Evaluating e-learning on an international scale: An audit of computer simulation learning materials in the field of dentistry - Ai Ohsato; Naoko Seki; Tam Thi Thanh Nguyen; Janelle Moross; Masayo Sunaga; Yuji Kabasawa; Atsuhiro Kinoshita; Ikuko Morio (Elsevier, 2022)
Background/purpose: Global networking and e-learning courses are an effective strategy for sharing educational content and there is potential scope to use e-learning technology in dental education. Therefore, this study aimed to explicate the challenges encountered in international e-learning use and decipher optimum solutions for disseminating course/systems on an international scale. Materials and methods: An e-learning course with four computer-assisted simulation materials developed among international faculties was provided to dental undergraduates at dental schools in Japan and Vietnam in 2020. A post-questionnaire survey plus pre- and post-tests were conducted to obtain learners' feedback and assess the success of the course's implementation. Results: Altogether, 41 students participated, with a response rate of 78.8%. The mean post-test score was significantly higher than that of the pre-test (p < 0.001). Students from both groups felt that e-learning was beneficial, useful for their future, and should be continued. Conclusion: This study showed that e-learning/course provision could be achieved at an international level by using a common online system, which is beneficial for students to gain a wider perspective and global dental education. Learners indicated that they learned without any major problems in learning operations. This type of educational material creation and course implementation is extremely important in global networking and dental education in the present era; and communication and cooperation between the faculties was important for course provision. More countries should be included in future studies to ensure that it has global application.